UPAYA MENINGKATKAN HASIL BELAJAR MEMBACA ITENSIF MELALUI PEMBELAJARAN KOOPERATIF MODEL QUANTUM TEACHING PADA SISWA KELAS IX.7 SMPN 3 SELAT TAHUN PELAJARAN 2020/2021 - Teklin Teklin (JURNAL ILMIAH EDUNOMIKA, 2022)
One of the spearheads of educational success is the educator or "teacher". Teachers have the responsibility to prepare lesson plans carefully so that the learning process goes well so that learning objectives can be achieved according to the plan. We realize it or not, the reality on the ground to the success of learning is still far from expectations. It is possible that many faktors are the cause, including the ability of teachers to master learning management is still less than optimal. The teacher is still the center of the learning process, so students are less empowered in their abilities and their activities are not paid attention to. Cooperative teaching combined with Quantum Teaching. It expresses how important an interesting form of learning is. Rewards and praise are one of the right ways to motivate students to learn. Moving the organs of the body through interlude games, games, for example, can be done in the form of Quantum Teaching. The purpose of this scientific article is to find out whether the cooperative learning model with Quantum Teaching can improve the activeness and learning outcomes of students at SMPN 3 Selat Class IX.7. The method used in compiling this scientific article is a literature study by collecting relevant literature based on the specified topic. Furthermore, all the data collected were analyzed using descriptive analysis techniques. The results of this scientific article research are the application of the cooperative learning model with Quantum Teaching can improve learning outcomes and student activity compared to conventional learning models.